2009
DOI: 10.1016/s0140-6736(09)60737-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy plus chemotherapy with or without surgical resection for stage III non-small-cell lung cancer: a phase III randomised controlled trial

Abstract: Background Concurrent chemotherapy plus radiation therapy (chemoRT) is the standard treatment for stage IIIA(N2) non-small cell lung cancer (NSCLC), a common disease entity. Phase II studies demonstrated feasibility of resection after chemoRT with encouraging survival rates. This phase III trial compared both approaches. Methods Patients with stage T1-3pN2M0 NSCLC were randomized before induction chemoRT (2 cycles of cisplatin and etoposide [PE] concurrent with 45 Gy RT). If no progression, arm 1 underwent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
996
14
57

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,325 publications
(1,098 citation statements)
references
References 23 publications
31
996
14
57
Order By: Relevance
“…[9][10][11][12] In particular, Albain et al recently reported a phase 3 study of concurrent chemoradiotherapy with or without surgical resection for stage IIIA, N2 NSCLC. 14 The median OS with and without surgery was 23.6 months and 22.2 months, respectively (P ¼ .24) and the median PFS was better in patients with surgery (12.8 months vs 10.5 months, P ¼ .017). In further exploratory analysis, the median OS was improved in the surgical group when a lobectomy was performed compared with a matched nonsurgical group (33.6 months vs 21.7 months, P ¼ .002).…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11][12] In particular, Albain et al recently reported a phase 3 study of concurrent chemoradiotherapy with or without surgical resection for stage IIIA, N2 NSCLC. 14 The median OS with and without surgery was 23.6 months and 22.2 months, respectively (P ¼ .24) and the median PFS was better in patients with surgery (12.8 months vs 10.5 months, P ¼ .017). In further exploratory analysis, the median OS was improved in the surgical group when a lobectomy was performed compared with a matched nonsurgical group (33.6 months vs 21.7 months, P ¼ .002).…”
Section: Discussionmentioning
confidence: 95%
“…However, the inclusion of surgical intervention into the treatment strategy for advanced-stage NSCLC has been reproducibly associated with improvements in survival [3][4][5][6][7][8]. Using data from population-based and institutional databases, we and others have demonstrated significantly longer cancer-specific and overall survival in advanced NSCLC patients treated with surgical intervention (alone or in combination) compared with nonsurgical modalities, including chemoradiotherapy, chemotherapy alone, radiotherapy alone, and no treatment (p < 0.001) [3][4][5][6].…”
mentioning
confidence: 88%
“…Survival for advanced-stage NSCLC is only 4%, and outcomes are generally governed by response to systemic therapy [1]. Yet, the inclusion of surgical therapy into multimodality treatment regimens has been reproducibly associated with improved outcomes [3][4][5][6][7][8]15]. A recurrent criticism of these studies is that the observation of improved survival with surgical intervention is attributable to selection bias for patients with favorable characteristics (fewer comorbidities, lower-volume disease) rather the surgical treatment.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Most phase II and III studies of induction chemotherapy or chemoradiation have shown prolonged survival compared with historical series and complete pathological response (i.e. no viable tumour) in 10-20% of patients [21,98,99].…”
Section: N2 Diseasementioning
confidence: 99%